Proceedings of the International Conference on Health and Well-Being in Modern Society (ICHW 2019) 2019
DOI: 10.2991/ichw-19.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic Behaviour and Assessment of the Quality of Life of Reproductive Age Women in Eastern Siberia

Abstract: The article analyzes the problem of alcohol behavior of women of reproductive age in Eastern Siberia and assessment of their quality of life. The authors analyze the current research of this problem and make a conclusion about the ambiguity of the solution of the problem of alcohol behavior in women and its connection with the quality of life. In a sample of 1,300 women (mean age 34.22±6.39), 816 of whom consumed alcohol, and 514 of whom consumed no alcohol, the authors conclude that women of reproductive age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…In reference to other study [24], we have shown in our study that women of reproductive age with PCOS are less likely to use roles attributed to female gender. However, we did not observe any negative emotions, experienced by women with PCOS in this respect.…”
Section: Resultssupporting
confidence: 67%
“…In reference to other study [24], we have shown in our study that women of reproductive age with PCOS are less likely to use roles attributed to female gender. However, we did not observe any negative emotions, experienced by women with PCOS in this respect.…”
Section: Resultssupporting
confidence: 67%
“…Many women believe that a glass of "high quality" alcohol (dry red wine) during normal pregnancy into the second trimester "will do no harm to the fetus or can even be healthy". Most obstetricians/gynecologists, pediatricians and other doctors, who are not directly involved in treatment of alcohol addiction, do not have any relevant experience in discussing alcohol consumption with women or screening women, who are at risk of having FAS/FASD children [33,34,40,9,10,37].…”
Section: Currently the Alcohol Consumption Level Inmentioning
confidence: 99%